BCPC Congress 2016. (1st December 2016) - Matthews, Graham; Blake, Robin
The theme of the BCPC Congress 2016 was "Changes in European agriculture, the regulatory environment and Brexit". By the time of the actual Congress, the UK had announced that the exit from the EU would be before the end of March 2017.